Benzodiazepines increase the likelihood of both infectious and thrombotic complications. Issue 1 (July 2021) - Skicki, Edward; Morgan, Madison; Brown, Catherine; Bradburn, Eric; Rogers, Frederick
Abstract : INTRODUCTION: Benzodiazepines (BZDs) modulate peripheral γ-amino-butyric acid type A on macrophages causing immunomodulation. They inhibit proinflammatory cytokines increasing infections. Prior studies have also shown that infections can increase thrombotic complications. We sought to examine this relationship in trauma patients. We hypothesized that the presence of BZDs on admission urine drug screen (UDS) would increase rates of both complications. METHODS: All patients submitted to the Pennsylvania Trauma Outcome Study database from 2003 to 2018 were queried. Those with a positive UDS for BZDs were analyzed. Infectious complications were defined as pneumonia, urinary tract infection, sepsis, wound, and soft tissue infection, and thrombotic complications were defined as presence of pulmonary embolism or deep vein thrombosis. Logistic regressions controlling for demographic and injury covariates assessed the adjusted impact of BZDs on infectious and thrombotic complications. RESULTS: A total of 3, 393 patients (2.08%) had infectious complications, and 3, 048 (1.87%) had thrombotic complications. Furthermore, 33, 260 patients (20.4%) had a positive UDS for BZDs on admission. Univariate analysis showed that those positive for BZDs had higher rates of infectious (3.33% vs. 1.76%, p < 0.001) and thrombotic (2.84% vs. 1.62%, p < 0.001) complications. Multivariate analysis revealed that BZDs significantly increased the odds of infectious and thrombotic complications. Patients who tested positive for BZDs and subsequently developed infection had increased odds (adjusted odds ratio, 1.65; p < 0.001) of developing thrombotic complications. CONCLUSION: Trauma patients with a positive UDS for BZDs had higher odds of both infectious and thrombotic complications. Moreover, odds of thrombotic complications were higher in those with infections. LEVEL OF EVIDENCE: Epidemiological, level III.